Analisis Faktor-Faktor Yang Mempengaruhi Invenstasi Asing Dan Investasi Domestik Di Indonesia Periopde Tahun 1990-2011 - Edalmen (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2013)
This study aims to determine the factors that affect foreign investment and domestic investment in Indonesia during the period 1990 to 2011. There are five independent variables used in this study, namely the gross domestic product (GDP), interest rate, money supply, wage rate and currency exchange rate. In this study, the dependent variable is foreign investment and domestic investment. Results of this study found that the variable GDP, interest rate, money supply, wage rate and currency exchange rate simultaneously (together) with a significant influence of foreign investment.